(untitled) (Research, Society and Development, 2025)
The objective of this study is to analyze the implementation of Multifunctional Resource Rooms (MRR) in the Municipality of Santa Bárbara do Pará, with an emphasis on the educational inclusion of students with disabilities. The study shows that there are few schools with MRR, and that the available infrastructure and resources are limited, affecting the quality of Specialized Educational Assistance (SEA). Teachers’ reports mention the need for continuous training and collaboration among education professionals. MRR are recognized as essential for ensuring the right to high-quality education, fostering diverse and welcoming school environments. The article proposes future directions, including resource training, improvement of MRR infrastructure, support for collaboration among educators, and the implementation of continuous assessment mechanisms. The conclusions highlight the importance of integrated actions to ensure that all students have access to inclusive education, respecting their individualities and contributing to a more just and equitable educational environment.